1985
DOI: 10.1136/thx.40.4.278
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sarcoidosis: alterations in bronchoalveolar lymphocytes and T cell subsets.

Abstract: Peripheral blood and bronchoalveolar lavage lymphocyte subpopulations have been evaluated in 14 patients with pulmonary sarcoidosis and eight normal subjects, monoclonal antibodies of the leu series being used. No significant alterations of T lymphocyte subpopulations were found in the peripheral blood of sarcoidosis patients. There was, however, a significantly greater proportion of T suppressor-cytotoxic cells (36.0 (SD 17-6%)) in the bronchoalveolar lavage fluid of patients than of normal subjects (15% (5.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Undirected biopsies yielded less positive results compared with those obtained from overtly affected organs; this was also reported for conjunctival granuloma or lacrimal gland biopsy 42-44. The analysis of fluids and cells obtained by bronchoalveolar lavage, including CD4/CD8 ratio, is not specific enough for the definitive diagnosis of sarcoidosis 45. Chest x ray usually shows hilar adenopathy in combination with interstitial lung disorder.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Undirected biopsies yielded less positive results compared with those obtained from overtly affected organs; this was also reported for conjunctival granuloma or lacrimal gland biopsy 42-44. The analysis of fluids and cells obtained by bronchoalveolar lavage, including CD4/CD8 ratio, is not specific enough for the definitive diagnosis of sarcoidosis 45. Chest x ray usually shows hilar adenopathy in combination with interstitial lung disorder.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Our findings are in conflict -regarding the T-cell segment of the alveolitis -with some previously pub lished reports of exaggerated T-cell activity in sarcoi dosis [30][31][32][33][34], To the best of our knowledge there are no studies available focusing on the alveolitis of the chronic form of the disease. Greenings et al [35] re ported a decrease of BAL lymphocytes in correlation to the duration of the disease and Hollinger et al [36] demonstrated that patients with inflammatory active sarcoidosis and low numbers of BAL lymphocytes have a high risk of treatment failure and subsequent development of chronic disease. The wide range of al terations in T-cell alveolitis found in the literature may be due to the amalgamation of patients with acute and chronic disease in groups with active and inactive sarcoidosis [15,16,21,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The lavage fluid was centrifuged at 500 g for five minutes to recover cells. 8 balanced salt solution and resuspended in RPMI 1640. The total cell count and the number of cells/ml of lavage fluid were obtained by using an Improved Neubauer counting chamber.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%